The Differences In Knowledge Improvement About Brushing Teeth Between Health Education With Pop Up Book And Video Media In Elementary School Children - Sunarto; Sherina Putri Nuswantoro; Sudiro (Future Science, 2025)
Background: Dental and oral health support health immunity and require attention because these problems need special treatment. Problems arise, one of which is caused by behavioral factors or attitudes that neglect cleanliness. Efforts to increase knowledge can be done in various ways, and providing health education through pop-up books and video media is one of the techniques. Objective: Determine the difference between pop-up books and video media in increasing knowledge about the health education of brushing teeth. Methods: A quasi-experiment will assess the conditions before and after testing. The sample consisted of 75 respondents, consisting of 35 respondents from the pop-up book media group (P) and 35 from the video media group (V). Results: The results of the Wilcoxon statistical test in the two intervention groups were obtained in the pop up book group with a mean value of 84.00 and the video group with a mean value of 87.43 The results of the Mann Whitney test were obtained with a significant difference in knowledge increase from the two groups with a value of 0.031 (p value > 0.05). Conclusions: Health education using video media is more effective in increasing knowledge of brushing teeth.